Acute exacerbation of Toxoplasma gondii infection after hematopoietic stem cell transplantation: five case reports among 279 recipients - Sumi, Masahiko; Aosai, Fumie; Norose, Kazumi; Takeda, Wataru; Kirihara, Takehiko; Sato, Keijiro; Fujikawa, Yuko; Shimizu, Ikuo; Ueki, Toshimitsu; Hirosima, Yuki; Ueno, Mayumi; Ichikawa, Naoaki; et al. (International journal of hematology, 2013)
Toxoplasmosis is a rare and possibly underestimated complication following hematopoietic stem cell transplantation (HSCT) associated with a high mortality rate, although the incidence of toxoplasmosis after HSCT in Japan has not been established. We retrospectively studied patients with toxoplasmosis after HSCT, and identified five patients who had been diagnosed with an acute exacerbation of toxoplasmosis among 279 HSCT recipients at our institution between 1998 and 2011, representing an incidence of 1.8 %. Among 87 autologous HSCT recipients, one definite case was diagnosed. The serological test for Toxoplasma gondii before HSCT was positive in 18 of 192 allogeneic HSCT recipients. Of the 18 seropositive patients, three had definite infections, and one had possible infection. All four definite cases were diagnosed at autopsy. In the definite cases, three allogeneic HSCT recipients had disseminated or pulmonary toxoplasmosis and one autologous HSCT recipient had toxoplasmic encephalitis, although toxoplasmosis was not suspected at the premortem examination due to non-specific clinical and radiological manifestations. Thus, acute exacerbation of toxoplasmosis should be suspected in recipients after HSCT. Early diagnosis and treatment for toxoplasmosis would certainly contribute to a decrease in mortality after HSCT.